Close Link Between Harmful Cyanobacterial Dominance and Associated Bacterioplankton in a Tropical Eutrophic Reservoir - Guedes, Iame A.; Rachid, Caio T. C. C.; Rangel, Luciana M.; Silva, Lúcia H. S.; Bisch, Paulo M.; Azevedo, Sandra M. F. O.; Pacheco, Ana B. F. (Frontiers in Microbiology, 2018)
Cyanobacteria tend to become the dominant phytoplankton component in eutrophic freshwater environments during warmer seasons. However, general observations of cyanobacterial adaptive advantages in these circumstances are insufficient to explain the prevalence of one species over another in a bloom period, which may be related to particular strategies and interactions with other components of the plankton community. In this study, we present an integrative view of a mixed cyanobacterial bloom occurring during a warm, rainy period in a tropical hydropower reservoir. We used high-throughput sequencing to follow temporal shifts in the dominance of cyanobacterial genera and shifts in the associated heterotrophic bacteria community. The bloom occurred during late spring-summer and included two distinct periods. The first period corresponded to Microcystis aeruginosa complex (MAC) dominance with a contribution from Dolichospermum circinale; this pattern coincided with high water retention time and low transparency. The second period corresponded to Cylindrospermopsis raciborskii and Synechococcus spp. dominance, and the reservoir presented lower water retention time and higher water transparency. The major bacterial phyla were primarily Cyanobacteria and Proteobacteria, followed by Actinobacteria, Bacteroidetes, Verrucomicrobia, and Planctomycetes. Temporal shifts in the dominance of cyanobacterial genera were associated with physical features of the water (retention time and transparency) and with shifts in the associated heterotrophic bacteria. The MAC bloom was associated with a high abundance of Bacteroidetes, particularly Cytophagales. In the second bloom period, Planctomycetes increased in relative abundance, five Planctomycetes OTUs were positively correlated with Synechococcus or C. raciborskii OTUs. Our results suggest specific interactions of the main cyanobacterial genera with certain groups of the heterotrophic bacterial community; the results suggest that considering biotic interactions may lead to a better understanding of the shifts in cyanobacterial dominance.